1998
DOI: 10.1038/nm0698-679
|View full text |Cite
|
Sign up to set email alerts
|

A role for carbohydrates in immune evasion in AIDS

Abstract: Rhesus monkeys were infected with mutant forms of simian immunodeficiency virus lacking dual combinations of the 4th, 5th and 6th sites for N-linked glycosylation in the external envelope glycoprotein of the virus. When compared with sera from monkeys infected with the parental virus, sera from monkeys infected with the mutant viruses exhibited markedly increased antibody binding to specific peptides from this region and markedly increased neutralizing activity. These results demonstrate a role for N-linked gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
473
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 533 publications
(490 citation statements)
references
References 26 publications
13
473
3
1
Order By: Relevance
“…Additionally, with simian immunodeficiency virus it has been shown that de-glycosylation events within the V1 region of the envelope result in a virus with increased antibody neutralization potential (61). With HIV-1, the N-linked glycosylation pattern has also been shown to have a varied effect on the induction of neutralizing antibodies (44,(62)(63)(64)(65)(66)(67).…”
Section: Figmentioning
confidence: 99%
“…Additionally, with simian immunodeficiency virus it has been shown that de-glycosylation events within the V1 region of the envelope result in a virus with increased antibody neutralization potential (61). With HIV-1, the N-linked glycosylation pattern has also been shown to have a varied effect on the induction of neutralizing antibodies (44,(62)(63)(64)(65)(66)(67).…”
Section: Figmentioning
confidence: 99%
“…For instance, interaction and fusion of the human immunodeficiency virus (HIV) with its target host cells is mediated by its envelope protein, gp160, which has over 50% of its mass comprising of glycans [7][8][9][10]. The high population and diverse range of glycans on this protein acts as a shield for the virus against the immune system; the glycans also mask epitopes that impact HIV disease progression [8,[11][12][13][14][15][16][17]. Consequently, conducting glycoproteomics studies on this target, defining the structures and locations of glycans in the HIV envelope protein, is important in understanding how variation in glycosylation affects the functions of this protein, and the studies may also provide valuable information that can be useful in identifying new vaccine candidates.…”
mentioning
confidence: 99%
“…However, viral attenuation in vivo correlated inversely with the degree of the SIV-specific antibody response and protection from the subsequent viral challenge (14). Attenuation was also achieved by deleting N-linked glycosylation sites in gp120 envelope protein (15,16), suggesting a more efficient eradication of deglycosylated viruses by antibody-and T cell-mediated immune response. Nevertheless, reversion of glycosylation site mutants was observed (15), indicating that viral replication still occurred despite the efficient immune control of deglycosylated SIV.…”
mentioning
confidence: 99%
“…Attenuation was also achieved by deleting N-linked glycosylation sites in gp120 envelope protein (15,16), suggesting a more efficient eradication of deglycosylated viruses by antibody-and T cell-mediated immune response. Nevertheless, reversion of glycosylation site mutants was observed (15), indicating that viral replication still occurred despite the efficient immune control of deglycosylated SIV. Here, we describe a gain-offunction strategy to generate a highly attenuated SIV strain endowed with a transcriptional repressor for studies in primate models.…”
mentioning
confidence: 99%